Survey results of the training, nutrition, and mental preparation of triathletes: Practical implications of findings - Dolan, S. H.; Houston, M.; Martin, S. B. (Journal of Sports Sciences, 2011)
Although triathlon is growing in popularity at a remarkable rate, it has not been extensively studied. The aims of this research were to identify preparation strategies used by triathletes and to categorize these strategies according to gender and consultation with triathlon coaches. Survey data collected from 401 triathletes (207 males, 194 females) revealed training, nutritional, and mental preparation habits. Most participants engaged in strength training, consumed food and/or fluids during and after training, set training and competition goals, and applied mental preparation strategies during training and the hour before racing. Water was the most commonly consumed fluid; positive self-talk was the most used mental strategy. Participants were more likely to consult with a triathlon coach than a nutrition or sport psychology professional. Athletes with more years of experience in triathlon and those competing in longer distances were more likely to consult a triathlon coach. Female triathletes were more likely than male triathletes to train with others, use mental preparation strategies, and report feeling anxious before competitions. More male triathletes reported using nutritional supplements during training than their female counterparts. These findings add to the limited research base on triathletes' training habits, and hopefully will help guide practitioners who work with this group. The results provide guidance for collaborative efforts among training, nutrition, and mental health professionals to best support triathletes.